LEGAL POSITION OF FOREIGNERS IN CROATIAN HISTORY – PAST LESSONS FOR CURRENT IMMIGRATION PROBLEMS (EU and comparative law issues and challenges series (ECLIC), 2019)
The European Union has been exposed to very dynamic social changes for the last decade, and the issues of migration, asylum, and the protection of the legal position of foreigners have become some of the most vibrant areas within the EU political agenda, in particular within the activities of the European Parliament. Relatively frequent migration policy changes within national legislation are the result of attempts to harmonize it with the recent EU acquis. In modern Croatian legislation, in accordance with the content of the applicable Aliens Act, there are visible attempts of legal balancing between the two dominant interests: the very extensive protection of social, political, economic, and other rights of immigrants and the security and protection of the national public policy. Nevertheless, understanding the legal position of foreigners in Croatian law demands consideration of various social and political factors and an extensive interpretation of the legal framework that has actively developed throughout history in our area. Taking into account the growing importance of immigration policy for the territory of the Republic of Croatia, the aim of this article is to determine the legal position of foreigners in the domain of private and public law throughout different periods of Croatian legal history and, ultimately, by comparing the results with the contemporary situation, question their continuity and offer some lessons for current immigration problems.